Post-influenza neuromuscular complications (Journal of Health Sciences, 2018)
According to the data of the World Health Organization, every year influenza develops in up to 1.575 billion people, and 1 million of them die. Although influenza viruses are the leading cause of the upper respiratory tract infections, severe neuromuscular complications occur as well, frequently leading to disability or even death. Children under five years of age and elderly people are at the highest risk of complications and mortality. The article discusses the selected neuromuscular complications of influenza, bringing particular attention to their etiology, symptomatology, diagnostics, and therapy.